INTERPRETASI PADA TOKOH SRIKANDI DALAM TARI SRIKANDI CAKIL SUSUNAN DIDIK BAMBANG WAHYUDI - Firdha, Agustin; Sulastuti, Katarina Indah (Institut Seni Indonesia Surakarta, 2024)
The character of Srikandi in the dance Srikandi Cakil by Didik Bambang Wahyudi portrays a Javanese woman who is graceful and charming yet has a masculine character that is agile, clever, and confident, capable of defeating opponents, including men. Srikandi is depicted as a firm and resolute figure. Agustin became interested in interpreting this character in her own dance. This research focuses on Agustin's interpretation and the process of interpreting the character of Srikandi in Srikandi Cakil. In discussing the form of the interpreted dance, the concept from Katarina Indah Sulastuti is used, covering elements of movement, makeup-costume, music, floor patterns, dramatic design, props, and performance space. Meanwhile, the interpretation process is based on Bahari's theory, which states that interpretation is the act of understanding the meaning, message, and values contained in a work. This research is qualitative, using the Practice Based Research method, with data collected through participatory observation, interviews, literature review, and document studies, and presented descriptively and interpretively. The research findings show that the structure of Agustin's interpretation of Srikandi in Srikandi Cakil remains grounded in the traditional Surakarta dance style. The interpretation develops elements of movement, music, floor patterns, and dramatic design. Movement interpretation is applied to the battle, dialogue (antawecana), and combat gestures in the song. Music interpretation includes adding dialogue, song (tembang/palaran), and a vocal segment (pocapan) at the end of the dance. Floor pattern interpretation involves adding curved lines. The interpretation process follows stages of preparation, exploration, dancer adaptation, work realization, rehearsal, evaluation, and presentation.